Does the AI need a genealogy? The ‘PAIA’ model and the question concerning technology for the ai regulation - Pisano, Aldo (Mechane, 2025)
This paper explores AI’s role through the lens of philosophical anthropology, examining its impact on cultural spaces and values. Technology, as Arnold Gehlen argues, is integral to human evolution, shaping culture as a ‘second nature’. Ivan Illich’s concept of the critical threshold warns that beyond certain limits, technology distorts rather than supports human and cultural systems. To avoid alarmism, AI should be understood within this continuum of technological development, familiarizing society with its potential without overlooking risks. The PAIA model (Pervasiveness, Autonomy, Invisibility, Adaptivity) provides a framework to assess these risks, ensuring AI does not replace human agency but enhances cultural resilience. The paper will try to provide an example on how intelligent technologies could generate a culture of Distrust in Generative AI Era. Nevertheless, the main objective of this paper remains to show a possible non-catastrophic perspective of a co-living culture between humans and AI.